Content Analysis of Islam Wasathiyah in the ISMUBA Teaching Materials for Senior High School Muhammadiyah Throughout Padang City - Delvina, Delvina; Novigator, Hendri; Afrizal, Afrizal (Program Pascasarjana UMSB, 2025)
The global rise of religious radicalism necessitates educational strategies promoting moderate Islam, particularly in Indonesia. Muhammadiyah addresses this through its ISMUBA curriculum (Al-Islam, Kemuhammadiyahan, Arabic), though systematic analysis of its content remains unexplored. This study evaluates the integration of Wasathiyah values (Tasamuh, Tawazun, Tajdid, Maslahah, ‘Adalah, Anti-Extremism) within ISMUBA textbooks used in Muhammadiyah senior high schools in Padang. Employing qualitative content analysis with triangulation (document analysis, classroom observation, and interviews), this research reveals a deliberate and multi-layered embedding of Wasathiyah values. Findings demonstrate explicit doctrinal framing in Kemuhammadiyahan, contextual integration in Al-Islam, and implicit transmission in Arabic materials, showcasing strong alignment with Muhammadiyah’s ideological mission of promoting progressive Islam. The study’s novelty lies in its systematic mapping of value representation and its methodological triangulation, addressing gaps in prior research focused solely on pedagogy or higher education. A key limitation is its exclusive focus on content and pedagogy, excluding student reception. Future research should investigate how students internalize these values across diverse socio-cultural contexts.